2009
DOI: 10.3748/wjg.15.4290
|View full text |Cite
|
Sign up to set email alerts
|

Does Helicobacter pylori eradication therapy for peptic ulcer prevent gastric cancer?

Abstract: AIM:To investigate the effects of Helicobacter pylori (H pylori ) eradication therapy for treatment of peptic ulcer on the incidence of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 13 publications
1
35
0
1
Order By: Relevance
“…Several studies have reported preventive effects of H. pylori eradication therapy against gastric cancers [1,8,9]. However, it has been clarified that primary or metachronous gastric cancers may be discovered even after successful eradication therapy [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported preventive effects of H. pylori eradication therapy against gastric cancers [1,8,9]. However, it has been clarified that primary or metachronous gastric cancers may be discovered even after successful eradication therapy [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Mabe et al [90] reported that cases of duodenal ulcer are more prevalent in younger individuals than gastric cancer cases and that gastritis in duodenal ulcer was primarily antral and spared the gastric corpus, allowing continued high levels of acid secretion. Corpus inflammation, however, has long been known to suppress acid, and low acid allows H. pylori to interact with the mucosa to cause more inflammation and to establish a vicious cycle leading to the loss of glands and to atrophy.…”
Section: Failure To Notice Lesionsmentioning
confidence: 99%